Determinants of Sales Volume in Es Teh Cup MSMEs: The Influence of Personal Selling and Distribution, Moderated by Packaging - Newton Newton; Agustini Tanjung; Helen Parkhurst; Felina Co Young (Oikonomia : Journal of Management Economics and Accounting, 2025)
The packaged cup beverage business is a phenomenon that is currently booming in Indonesia due to its tropical climate.  Beverage packaging served in cup packaging is very suitable for today's practical culture. Tea is one type of drink that is served in cup packaging because it is very easy to make compared to other types of drinks. This study aims to determine the effect of personal selling and distribution costs on the sales volume of cup iced tea businesses, and to determine the role of packaging as a moderating variable that strengthens the relationship between the two variables on sales volume. This study uses a quantitative approach with 300 respondents of cup iced tea MSMEs in Bekasi City. Data were collected through questionnaires and analyzed using the Structural Equation Modeling (SEM) method with the help of SmartPLS version 3.0 software. The results showed that personal selling and distribution costs have a positive effect on sales volume. Packaging is proven to strengthen the effect of personal selling on sales volume, although the effect is not too strong. However, packaging does not strengthen the effect of distribution costs on sales volume. This finding shows the importance of a marketing strategy that does not only rely on promotion and distribution, but also pays attention to the design and function of packaging as part of the product's appeal.